Relationship between patient-reported outcome measures (PROM) and three measures of foot–ankle alignment in patients with metatarsal head pain: a cross-sectional study. Issue 1 (December 2016) - González-Sánchez, Manuel; Velasco-Ramos, Esther; Muñoz, Maria; Cuesta-Vargas, Antonio
Abstract Background The aim of the present study is to establish the relationship between foot–ankle patient-reported outcome measures (PROM) and three measures of foot–ankle alignment (MoFAA) in patients with metatarsal head pain. Methods A cross-sectional study where 206 patients completed three PROMs and a clinician recorded three MoFAA bilaterally (three times each). A reliability analysis of the MoFAA, a correlation analysis (between MoFAA and PROM) and regression analysis (dependent variable: PROM; independent variables: MoFAA) were performed. Results Pearson's coefficient changed in each PROM used, ranging from 0.243 (AAOS-FAMShoeComfortScale –FVARight ) to 0.807 (FFIIndex –first MTPJEright ). Regression indices (R2 -corrected) ranged between 0.117 (AAOS-FAMShoeComfortScale ) and 0.701 (FFIIndex ). Conclusions The MoFAA correlated between moderately to strongly with the foot–ankle PROM selected. The level of correlation between MoFAA and PROM was higher when patients with metatarsal head pain were asked about foot health status, pain and function; however, the correlation was poor when the patient was asked about shoe aspects. In addition, the MoFAA variable that achieved the highest correlation value was the first metatarsophalangeal joint extension. The results obtained in this study could be used in future studies to develop tools for assessing and monitoring patients with metatarsal head pain.